Avaliação da frequência de coletas de sêmen em machos reprodutores suínos no início da vida reprodutiva - Dornelles, Julianni (2019)
In breeding pigs, with the specific advances in genetics and demand of the swine market, it is necessary to evaluate if it is possible the greater use of the young animals and with that increase the production of inseminating doses and to maximize their useful life in the centers of artificial insemination .Therefore, the objective of this study was to evaluate the best intervals for the collection of semen from boars at the beginning of their reproductive life, at nine months of age. For this, twenty boars were randomly distributed in four treatments (T), being T1 - interval between collections of two days; T2- interval between collections of three days; T3- interval between collections of four days and T4- interval between collections of seven days (control). The ejaculates were diluted in Vitassem® (long acting diluent), and inseminating doses were produced, which were evaluated for the volume, total motility, mass motility, total concentration, , total number of cells, morphology, membrane integrity and reactive substances to thiobarbituric acid (TBARS) The inseminated doses were evaluated at hours 0, 24, 72, 120 and 168) and testicular measurements (length, width and volume). The T3 group presented a spermatic concentration of 5.6% (p> 0.05), 37.04% (p <0.05) and 42.15% (p <0.05) higher than T4, T2 and T1. The total motility of T4 was higher in 0.79% (p> 0.05), 2.02% (p> 0.05) and 3.38% (p <0.05) than in T3, T2 and T1, respectively. The right testicle volume in the T4 was 18.48% (p <0.05), 23.14% (p <0.05) and 34.46% (p <0.05) compared to T3, T2 and T1, respectively. In the evaluation of sperm morphology for normal cells, T4 was higher in 6.47% (p <0.05), 8.14% (p <0.05) and 14.21% (p <0.05) when compared to the groups T3, T2 and T1. The T4 group had normal plasma membrane integrity (p <0.05), 8.8% (p <0.05) and 14.57 (p <0.05) plasma membrane integrity when compared to T3, T2 and T1. And for the Tbars parameters, the T1 group was 6.58% (p <0.05), 12.52% (p <0.05) and 10.03% (p <0.05) higher than the groups T2, T3 and T4, respectively. These results indicate that short intervals between semen collections negatively influence the quantitative and qualitative characteristics of sperm cells. The four day interval between collections provides the best results on sperm viability.